Artificial Intelligence in HR: Legal and Ethical Aspects of Application and Possibilities of Regulation in Different Labor Markets - Sereda, Olena H.; Lutsenko , Оlena Yе.; Nesterovych , Oleksii S.; Shvets , Nataliia M.; Hryhorenko , Dmytro A. (PRAWO i WIĘŹ, 2026)
The paper’s purpose involves identifying the legal and ethical aspects of artificial intelligence applied in HR and considering the possibilities of regulating this process in different labor markets. This paper defines how AI affects recruitment, performance evaluation, and HR management. This paper considers the need to create international standards and agreements governing AI applications in HR management that would be the legal ground for safeguarding employees’ rights and strike a balance between automation and human factors. The results reveal that AI significantly improves recruitment efficiency and decision-making capabilities in HR by automating candidate screening and analyzing large datasets. The research concludes that successful AI implementation in HR requires balancing technological innovation with ethical and legal considerations. Clear regulations governing the roles and responsibilities of AI developers, operators, and users are essential to prevent discrimination and ensure data privacy. These findings have broader implications for other sectors, such as healthcare and education, that are looking to integrate AI technologies.